A Lesson Learnt from a Dural Carotid Cavernous Fistula-induced Superior Ophthalmic Vein Occlusion with Posterior Ischaemic Optic Neuropathy. (4th May 2022) - Hoang, Tung Thanh; Nguyen, Cuong Ngoc; Ha, Thanh Thien Huy; Subramanian, Prem S.
ABSTRACT: We report a 64-year-old male patient without any contributory medical history who visited the eye clinic due to right-sided headache for 1 month and then loss of vision for 3 days. The clinical presentation suggested a cavernous sinus syndrome and acute optic nerve ischaemia in his right eye. The left eye was normal. Orbit and brain magnetic resonance (MR) imaging demonstrated restricted diffusion of the posterior orbital segment of the right optic nerve, suggesting an acute posterior ischaemic optic neuropathy. Three-dimensional time-of-flight MR angiography showed high flow in the right cavernous sinus, indicating a carotid cavernous fistula (CCF). In the arterial phase of digital subtraction angiography (DSA), a fistula in the right cavernous sinus was revealed which was fed by meningeal branches from both the external and internal carotid arteries, confirming an indirect CCF. The origin of the right ophthalmic artery was seen, but its branches were not detected. Right common carotid artery DSA showed a superior ophthalmic vein occlusion and the drainage vein of the CCF ran through the inferior petrosal sinus to the internal jugular vein. The right cavernous sinus was embolised using platinum coils and glue to occlude the feeding vessels from the branches of both the external and internal carotid arteries. Post-embolisation imaging showed complete closure of the fistula.